URODYNAMICS UTILITY PATTERN AMONG INDONESIAN UROLOGISTS - johanes, charles; Wibisono, Elita; Rahardjo, Harrina Erlianti (Indonesian Urological Association, 2016)
Objective: Aim of this study was to describe urodynamic utility pattern among Urologists in Indonesia especially in treating lower urinary tract symptoms (LUTS), urinary retention, overactive bladder (OAB), stress urinary incontinence (SUI) and urologic pediatric cases. Materials & methods: Subjects were Indonesian Urologists who attended urological scientific meetings or workshop in Jakarta between February-July2014. They were given questionnaires about urodynamics and its indications. Results: One hundred and eight Urologists completed and returned the questionnaires out of 303 Urologists in Indonesia. Thirty eight Urologists worked at hospitals where urodynamic machine is available, the rest sent their urodynamic cases elsewhere. Most of Urologists ordered urodynamics for LUTS patients with neurological deficit (84.3%) and weak anal sphincter tone/bulbocavernosus reflex (62.0%). In OAB cases, urodynamics was used in cases with failure of medical therapy (70.4%) and neurological deficit (68.5%). Two most common indication criterias in SUI cases were failure of conservative therapy (70.4%) and mixed incontinence cases (SUI with OAB) (60.2%). Neurological deficit (66.7%) and urinary incontinence (26.9%) were the most frequent urodynamic indications applied in children. Conclusion: We described the urodynamic utility pattern among Indonesian Urologists. Availability of urodynamic machine, patient economic capabilities, guideline availability on urodynamics could be the factors affecting this pattern.